Factors That Determine Farmer Participation Rate In The Farmer Group - Latarus Fangohoi; Yohanis Y. Makabori; Yuliana Ataribaba (Politeknik Negeri Lampung., 2023)
Participation is the encouragement and mental involvement of a person to contribute. Be responsible for his group and increase awareness. Organize groups where individual characteristics differ from one another. The purpose of the study was to determine the level of farmer participation and the relationship between the characteristics of farmer group members. The method of determining respondents using the census method. Analyzing the relationship between the dependent variable and the independent variable, using the Spearman Rank test method. The extension evaluation method used a standard T-score and the data were analyzed descriptively. The results of this study indicate that the level of participation of farmers in planning and implementation has a very high level of participation. The level of participation of farmers in the evaluation stage is high and the level of participation of farmers in the stage of enjoying the results is very high. The results of the interaction of internal factors and external factors have a fairly strong and unidirectional relationship level so that H0 is rejected and Ha is accepted. Keywords: Correlation, External Factor, Internal and Participation